2022
DOI: 10.1039/d2ta04108a
|View full text |Cite
|
Sign up to set email alerts
|

Strain tunable nanoporous r-N-GDY membrane for efficient seawater desalination

Abstract: Seawater desalination is believed to be the most promising solution to solve the current crisis of global freshwater deficiency. The applications of nanoporous graphene filters and biological water channels have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the genesis of increased barriers can be attributed to ion dehydration, which results in the unfavorable selection of ions. 62–64 As shown in Fig. S3,† the energy barriers for ions in this filter also primarily stem from ion dehydration.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that the genesis of increased barriers can be attributed to ion dehydration, which results in the unfavorable selection of ions. 62–64 As shown in Fig. S3,† the energy barriers for ions in this filter also primarily stem from ion dehydration.…”
Section: Resultsmentioning
confidence: 94%
“…Finally, we conducted a comparative analysis of the filtration performance of multilayer ABBPM membranes in this paper against various RO membranes, including four conventional RO membranes (including MFI zeolite, 73 commercial polymeric seawater RO, 74 nanofiltration, 75 and high-flux RO 74 ), three 2D monolayer membranes (porous graphene, 68 porous MoS 2 , 68 and r-N-GDY 64 ) and several multilayered structures (3L Cu-HAB MOF, 19 3L Ni-HAB MOF, 19 3L NiIT MOF, 62 and 3L NiAT MOF 62 ). These comparisons are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Former researches have demonstrated a robust correlation between permeance and nanopore size and shape on a membrane. ,, Specifically, by utilizing the high mechanical flexibility of the r -N-GY monolayer, tensile strain holds promise as an effective means for tailoring the pore size and shape to further enhance He permeance. In this study, uniaxial strain was applied to the r -N-GY monolayer along either the ZZ or AC direction, resulting in significant porous structural changes, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the r -N-GY membrane has a high mechanical flexibility with critical strain up to 44%. Thus, the pore size is highly tunable by applying external tensile strain that has been demonstrated to be efficient in controlling the water permeability for the case of r -N-GDY filter with a similar rhombic pore structure . Given the high structural stability of r -N-GY and great success of tunable 2D membranes in He purification, the performance of r -N-GY in He purification under the regulation of exterior tensile strain is highly expected and surely deserves further studies.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the water permeabilities of the graphene foam and graphyne membranes are two orders of magnitude larger, and even three orders of magnitude as compared to conventional polyamide membranes 27 (see Table 1 for a comparison). While tension can be used to enlarge the pores of graphene foam membranes and some two-dimensional materials, 28,29 pore size reduction for perfect salt rejection (the most challenging issue of the next generation of membranes) by compression is only possible in the case of graphene foam membranes. While the pore size of graphene foam membranes can be controlled by compression due to buckling of the graphene skeleton (resulting from the atomic thickness of graphene), it is impossible to control the pore size of graphyne or any other two-dimensional material by compression due to the possibility of out-of-plane buckling.…”
Section: Resultsmentioning
confidence: 99%